PENGGUNAAN MODEL ELPSA DENGAN BANTUAN ALAT PERAGA GEOBOARD PADA MATERI BANGUN DATAR SEGI EMPAT - Lilik Firdayati (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2019)
In fact, most of studens thought that Mathematics is difficult,  because  the instruction was dull, teacher was less  active as facilitator in instruction, teacher did not apply imstructional media, teacher didnot involve students enough  in instruction, too many formula but less in practice and also teacher did not maximalized instructional model, as the result, the instruction was ineffective, besides teacher was focuse more  on cognotive oriented domain at class instruction, he left students' affective and pshycomotor domains, so that, their maturnity was less maximal. The objective of study wad to improve students' activities and the  mathematics'score  through geoboard instructional aid. The research was done at seventh hrade of SMP N 3 Metro Lampung on April 2018. It was a Classroom  Action Research. Data collection were observation sheets, tes and questionnaire that was students' response to instruction. It was analysed through descriptive analytic technique. The result of study was the using of  ELPSA model through geoboard assisstance at two dimentional figure could improve the avetage value 55.36 % at cycle I  into 74.49% at cycle ll, and the average result value was 55.06 at cycle ll became 67.41 at cycle ll. Based on the data finding, it can be infered that in appliying mathematis at class teacher should motivate students' interest and also fix the quality of instruction through variation of instructional model and suitable teaching aid,so that students' result can be maximazed